A revision of the genus Extenuipalpus Reck, 1959 (Trombidiformes: Tetranychoidea: Tenuipalpidae), with description of a new species - Beard, Jennifer J.; Ueckermann, Edward A.; Castro, Elizeu B.; Seeman, Owen D. (Zootaxa, 2024)
Extenuipalpus is reviewed, covering its taxonomic history, a new genus diagnosis, body and leg chaetotaxy, and redescriptions of the three previously known species E. niekerkae (Meyer, 1979), E. quadrisetosus (Lawrence, 1940) and E. sagittus (Meyer, 1993) based on type material. We also describe a new species, E. situngu Beard & Ueckermann sp. nov. from glossy forest grape, Rhoicissus rhomboidea (E. Mey ex Harv.) Planch. (Vitaceae), and provide a key to species of Extenuipalpus.